TRANSFORMASI PENDIDIKAN DAN PEMBELAJARAN EKONOMI DI KALANGAN ANGGOTA KSU “Jaya Abadi” DI DESA BENDOSARI KECAMATAN SANANKULON KABUPATEN BLITAR - Dian Afidatur Rufaidah; Agung Haryono (Universitas Negeri Malang, 2015)
This study uses qualitative research with a phenomenological approach (naturalistic). Dig up information about the economic transformation of education and learning among members of the KSU